The Gracie Allen murder case : a Philo Vance story - Van Dine, S. S., 1888-1939 (P.F. Collier & Son Corporation, 1938)
The zany plot follows nitwit Gracie Allen trying to help master sleuth Philo Vance solve a murder.Allen's uncle fixes her up with Bill at a company picnic.When the two go out to a nightclub that night, Gracie inadvertently links Bill to the murder of a thug after finding the dead body and Bill's cigarette case at the scene of the crime.While being questioned at the club, she meets Vance who's investigating the homicide.After Gracie's bungled attempts to solve the case, Vance decides it might be easier to have her working with him.Despite Gracie's "help," the two eventually find the real killer.